1983
DOI: 10.1080/15287398309530426
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of dihydrocitrinone, a urinary metabolite of citrinin in rats

Abstract: Dihydrocitrinone, 3,4-dihydro-6,8-dihydroxy-3,4,5-trimethylisocoumarin-7-carboxylic acid, was isolated and identified as a urinary metabolite after oral administration of citrinin to rats. Male and female Osborne-Mendel rats received 30 mg citrinin/kg body weight by oral intubation. The metabolite dihydrocitrinone was present in urine collected at 0-2, 2-4, 4-6, 6-8, and 8-24 h after treatment. Only unchanged citrinin was found in blood collected 24 h after administration of the compound. The metabolite had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…Literature on the toxicokinetics and metabolism of CIT in humans is very scarce. However, Dunn et al [32] isolated and successfully identified dihydrocitrone as the main urinary metabolite of CIT in rats. Low levels (2-5 ng/mL) of the un-metabolized toxin were also detected in the urine of humans [33], indicating a possible but low level of excretion.…”
Section: Introductionmentioning
confidence: 99%
“…Literature on the toxicokinetics and metabolism of CIT in humans is very scarce. However, Dunn et al [32] isolated and successfully identified dihydrocitrone as the main urinary metabolite of CIT in rats. Low levels (2-5 ng/mL) of the un-metabolized toxin were also detected in the urine of humans [33], indicating a possible but low level of excretion.…”
Section: Introductionmentioning
confidence: 99%
“…It is conceivable that the dealkylation achieved by EC may also take place in biological systems during the enzymatic oxidation of CIT and is of particular importance concerning the poor data conditions of CIT metabolites. Relatively well understood is the CIT-derived metabolite dihydrocitrinone which has been found to be a major metabolite in the urine of rats [21] and humans [22]. Whether the m/z 267 detected by using EC/ESI-MS is dihydrocitrinone needs to be confirmed by structural elucidation.…”
Section: Resultsmentioning
confidence: 98%
“…Berndt and colleagues (Berndt and Hayes, 1982;Berndt, 1983) support the theory that citrinin itself is responsible as no renal metabolism of citrinin could be detected in their investigations. In contrast, the presence of the urinary metabolite dihydrocitrione has been demonstrated (Dunn et al, 1983), however, only 10 to 20% of citrinin is excreted as metabolites hence the possible role in renal toxicity is as yet, unknown.…”
Section: Mechanism Of Actionmentioning
confidence: 94%